Polypharmacy and falls in older people: Balancing evidence-based medicine against falls risk - Zia, A.; Kamaruzzaman, S.B.; Tan, M.P. (Taylor & Francis, 2015)
The term polypharmacy has negative connotations due to its association with adverse drug reactions and falls. This spectrum of adverse events widens when polypharmacy occurs among the already vulnerable geriatric population. To date, there is no consensus definition of polypharmacy, and diverse definitions have been used by various researchers, the most common being the consumption of multiple number of medications. Taking multiple medications is considered a risk factor for falls through the adverse effects of drug–drug or drug–disease interactions. Falls studies have determined that taking ≥ 4 drugs is associated with an increased incidence of falls, recurrent falls, and injurious falls. In light of existing evidence, careful and regular medication reviews are advised to reduce the effect of polypharmacy on falls. However, intervention studies on medication reviews and their effectiveness on falls reduction have been scarce. This article reviews and discusses the evidence behind polypharmacy and its association with falls among older individuals, and highlights important areas for future research.